Reconstructing identity and logic through the implementation of accrual accounting in Malaysia: An intra-organisational analysis - Rozaidy Mahadi; Siti Nabiha Abdul Khalid (Springer New York, 2021)
The purpose of this paper is to explain the change to accrual accounting in the Malaysian public sector, examined through the transition of institutional logics at intra-organisational levels, which effected changes in the public sector identity’s construction from independence in 1957 until the implementation of accrual accounting. A qualitative approach was used in this study, with the data being mainly derived from interviews with the relevant actors involved. Substantive data from documentation reviews were utilised to capture the development of institutional logics in the Malaysian government and the Accountant-General Department. The change to accrual accounting in Malaysia was precipitated by the transition in logics that resulted from the change from a bureaucratic to a managerialist administration. The introduction of accrual accounting as a new accounting practice represents a tool of change that bridged the variant of logics occurring between the governmental level and departmental level, and, at the same time, it has become a mechanism for reconstructing desired identities and practices.